PARADIGMA HUBUNGAN AGAMA DAN NEGARA - Zulkifli Zulkifli (JURIS (Jurnal Ilmiah Syariah), 2018)
There were three paradigm of relationship between religion and state. The first kind was integrated paradigm. This dealed with the relationship between religion (including political issue) and state. This paradigm was represented by ‘Syiah’ and ‘Sunni’. The second kind was symbolic paradigm. This kind dealed with the mutual relationship between religion and state in which religion could be developed because of the state existency, and the state also could be developed because of the religion. This paradigm supported by M. Mawardi Al-Ghazali. The last kind was secular paradigm. This kind opposed integreted and symbolic paradigm. This paradigm was supported by Ali Abdul Raziq.